Scattering of Electromagnetic Waveson Lattices of Rectangular Dielectric Resonators - О. О. Трубін (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2021)
The c-functions that determine the degree of influence of an external exciting electromagnetic field on a rectangular dielectric resonator (DR) in open space are calculated and investigated. The presence of directions with ''zero'' projection of the exciting electromagnetic field onto the DR field is shown. Using the perturbation theory, the spatial distribution of the scattered electromagnetic fields, which arises when a plane electromagnetic wave of p-, or s-type, is incident on a square lattice of rectangular dielectric resonators is studied. An electromagnetic model of scattering on a rectangular DR lattice is constructed. The appearance of a reflected and shadow lobe during scattering by a lattice of rectangular DRs with basic magnetic modes is demonstrated. The features of scattering by a cubic lattice with degenerate magnetic oscillations of the main type are investigated. It is shown that the degeneracy of the eigenoscillations of the resonators leads to a more complex scattering pattern: the appearance of additional lobes, as well as a change in their shape. It is noted that the shape of the spatial distribution of the scattered electromagnetic field of the grating can change noticeably with frequency variation within the frequency band of coupled oscillations of the resonators of the lattice. The obtained practical simulation results make it possible to significantly reduce the computation time and optimize complex multi-cavity structures of microwave and optical communication systems that simultaneously perform the functions of separation or combining of channels.